Mechanical Testing of Plastoceramic (nPMC Sheet- SiC Reinforced Polyester Nano Composite) - Selvam, R; Ravi, S; Balasubramanian, K (International Journal of Engineering and Technology, 2018)
Concept of nano-composite Technology has gained greater momentum inÂ its recent engineeringÂ applications. Recent works on Nano-composite technology have proved the viability of its use and its importance in modern engineering fields of applications particularly in the field of materials and manufacture. Â When dissimilar materials are used with different compositions to obtain newer nano- composite materials, it has lead to the production of novel products with unique properties. Â Â In the present study, the ceramic material SiC is used as reinforcement owing to its superior properties such as hardness, thermal conductivity and strength. And this has paved the way for using it in the making of polyester nano- composite sheet (nPMC) with aforementioned properties. Fabrication and characterization of Nano-composite sheet is carried out using a weight ratio of 30%Â so as to understand the molecular structure and mechanical behavior under external load. The synthetic procedure and characterization used in this study has made it possible to obtain Â SiC nano particles reinforced polyester nano-composites Â (nPMC) film with good thermal strength and chemical homogeneity over the traditional composite.Â Â